BUKU TERJEMAH KITAB TA’LIMU AL-MUTA’LIM; ANALISIS TEKS TERJEMAHAN ARAB-INDONESIA - Nisak, Umi Choirun; Taufiq, Mirwan Akhmad (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
This study discusses the analysis of the book translation of the book Ta'lim Muta'allim published by al-Hidayah. The book is one of the santri (moslem student) reference books to support students' understanding of the pesantren (Islamic boarding school) curriculum which uses the yellow book in their learning. The yellow book uses Arabic, so the translation of the book becomes very important. The focus of this research lies in the pattern of translation errors and justification of translations in accordance with the rules of Arabic and Indonesian dealing with lexicon, syntax and semantics. This qualitative research method uses an applied linguistic approach that focuses on error analysis. The primary data source in this research is the book translation of Ta'lim Muta'allim published by al-Hidayah, while the secondary data used in the study is a documentation technique by studying books and literacy that discusses the technique of translating properly and correctly according to structural , semantic and precise in terms of terminology. The results showed, including: Errors in the preparation of sentences in the target language, errors in the use of sentence effectiveness, errors in translating vocabulary, errors in aspects of omission or not translating aspects of vocabulary, phrases and sentences and errors in translating foreign terms.